(untitled) (Pharmacy Practice, 2022)
Objectives: To examine the pattern, nature, and attitude towards herbal medicines usage in the UAE. Methods: A cross-sectional national questionnaire was distributed over five weeks in 7 emirates of UAE: The questioner was constructed using an online platform and delivered randomly to 448 adults in the UAE. The data collection technique adopted for this study was a convenient sampling. SPSS version 24 was used for statistical analysis. Results: Among participants, 98.7% used herbal medicines (HMs), and respondents who aged between 18 and 24 years were more likely to use HMs. Participant were mainly female (70.3%), with fair health status (55%), and participant with chronic disease were significantly less likely to use HM (10.9%). The majority of herbal medicine users believed herbal medicine were harmless, because they were derivatives of natural products. The findings of this study reported that many participants use HMs to enhance immunity (26.8%), and for relaxation (23.5%). Conclusion: Despites the risk of adverse-effects, many participants in this study are regular users for HMs and have perception that 89 may cure or prevent COVID-19. Therefore, awareness-raising campaigns that target HM users are essential to mitigate any unwanted consequences.